PLANNING FOR TEACHING AND LEARNING: UNDERSTANDING AND WORKING WITH SYLLABI USED IN SCHOOLS, LYCEUMS, AND COLLEGES. WHAT GOES INTO LESSON PLANNING AND LESSON PLANS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Lesson planning is one of integral aspects of teaching English overseas, however it’s likewise one of the most time-consuming and tedious. Many plans even involve certainly whatthe instructor should say during a class, and the anticipated response from students. This article discusses the peculiarities of lesson planning on English language.